Some aspects of the attitude of teachers towards the introduction of inclusive education in general education schools - Shkutina, L.A.; Danek, J.; Rymkhanova, А.R. (Publ.KarSU, 2017)
The article contains an analytical review of the scientific literature of the countries of near and far abroad, as well as Russian literature devoted to the study of the attitude of teachers towards inclusive education. A comparative analysis of the results of a large number of studies has been carried out, where different positions of teachers have been identified in relation to inclusive education, including in relation to children with special educational needs and to the introduction of innovations in the educational process as a whole; There are a number of factors that affect the attitude of teachers towards the above objects and the ways of solving the current problem as one of the most urgent in the modern educational system. Тhe authors point out the need for special efforts to change the attitude of teachers to inclusion as a special form of organization of the educational process, i.e. Teaching teachers of general education institutions with the involvement of teachers of correctional and general schools implementing an inclusive approach; providing informational and consultative support for this process with the aim of creating a tolerant attitude in society towards children with disabilities. The formation of a positive attitude of teachers towards a system of inclusive education can be a guarantee of successful implementation and development of inclusive practice.
Мұғалімдердің жалпы білім беретін мектептерге инклюзивті білім беруді енгізуге деген қатынастарының жеке аспектілері
Отдельные аспекты отношения учителей к внедрению инклюзивного образования в общеобразовательные школы
Keywords: inclusive education; pedagogue; attitude; cognitive component; affective component; behavioral component